Pembakaran Lahan Dalam Regulasi Lingkungan Hidup - Verdinan, Verdinan; Eddy, Triono (Widya Yuridika, 2024)
This research seeks to thoroughly investigate the deficiencies in the legal framework surrounding corporate criminal liability for the burning of plantation land and comprehensively discuss legal policies for handling land burning crimes that result in the destruction of forest ecosystems. This research is normative juridical in nature, utilizing a descriptive-analytical approach. It examines existing legal issues and symptoms, assessing them against established laws, regulations and legal norms. The findings of this article indicate that the enforcement of corporate criminal liability for plantation land burning remains significantly weak due to selective law enforcement process against corporations and the imperfection of formal legal arrangements regarding the mechanism of criminalizing corporations as perpetrators of crimes holistically. Legal policies in handling land burning crimes that result in the destruction of forest ecosystems are carried out through penal efforts (enforcing criminal provisions related to land burning in the Law on Environmental Protection and Management, the Forestry Law and the Plantation Law) and non-penal including education, increasing awareness and community participation, empowering information technology, compiling a framework to support transparency, accountability and corporate social responsibility to preserve the environment.